2007
DOI: 10.1007/s11249-007-9216-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Evolution of Sliding Metal Surfaces During Running-in

Abstract: We studied the formation of tribologically induced nanocrystalline layers in lubricated contacts during running-in using a pin-on-disk tribometer coupled to a radionuclide high-resolution wear measurement system. The experiments were stopped after different running times and the sliding surfaces were analysed by atomic force microscopy, auger electron spectroscopy and focused ion beam analysis. Initially, at very high wear rates, zinc phosphate anti-wear films are formed in the contact regions of the surfaces,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…the attached fish-scale-like material. These evolutions have been reported in the tribofilm formation of metallic and ceramic materials [2][3][4][5][6][7][8][9][10][11][12][13][19][20][21][22][23][24]. In brief, the external frictional energy provided to the sliding wear results in (1) powdering and eventually amorphorization of the entrapped wear debris agglomerates, (2) shearing deformation/flow within the agglomerates and (3) tribo-oxidation.…”
Section: Origin Of Friction In Running-in Sliding Wearmentioning
confidence: 58%
See 3 more Smart Citations
“…the attached fish-scale-like material. These evolutions have been reported in the tribofilm formation of metallic and ceramic materials [2][3][4][5][6][7][8][9][10][11][12][13][19][20][21][22][23][24]. In brief, the external frictional energy provided to the sliding wear results in (1) powdering and eventually amorphorization of the entrapped wear debris agglomerates, (2) shearing deformation/flow within the agglomerates and (3) tribo-oxidation.…”
Section: Origin Of Friction In Running-in Sliding Wearmentioning
confidence: 58%
“…4b, c and 6a). Such wear particle generation through brittle fracture was widely reported in the wear of many other ceramics [4][5][6][7][8][9][10][11][12][13].…”
Section: Wear Mechanisms Taking Place In the Running-in Periodmentioning
confidence: 68%
See 2 more Smart Citations
“…As Dienwiebel et al showed for a lubricated chromium-cast iron contact with a contact pressure in the MPa range, that the question whether the film is on top or underneath can be answered by analyzing the energy consumption during film formation-very often during running-in-and by observing the changes of surface, microstructure and chemical composition of the near-surface as function of time [1]. For MPa systems in the initial stage of their running-in and highly-loaded contacts (GPa) like gears, the materials tend to develop protective films, commonly containing Zn, P and S from extreme pressure additives.…”
Section: Introductionmentioning
confidence: 99%